PARIWISATA DAN KETAHANAN SOSIAL BUDAYA - Saryani _ (Jurnal Ketahanan Nasional, 2013)
This study aimed to determined the extent of the development of tourism in Yogyakarta Special Region in retention to social-cultural resilience. And this was a descriptive study presented by using observation and questionnaires to found data and primary literature for secondary data. Furthermore, re search results illustrated that the development of Yogyakarta province would work well because the image of the region and the support facilities and infrastructure. On the other hand turned in its development results obtained proved less satisfactory still seen a serious lack in the maintenance of an object the absence of guarantee that the maximum safety for the tourists, a lot of changes in people's life as multidimensional crisis, which impacted on the image of tourism Yogyakarta Special Region, which in turn affected the social-cultural resilience.Keywords: Tourism, Social Cultural Resilience.